Analysis of electoral behavior in the city of Cali using fuzzy sets. Elections for municipal mayor 2003-2011 - Abadía, Adolfo A. (2015)
This paper aims to demystify, empirically, a statement widely shared in the political imaginary of the citizens of Santiago de Cali: candidates, who predominate in the popular sectors of the population, are the ones who win the elections for mayor («Aguablanca elects the mayor»). From an analysis with Qualitative Comparative Analysis (QCA) in their mode of fuzzy sets, it is shown that there are more complex scenarios of the electoral behavior in the elections for the municipal mayor in 2003, 2007 and 2011. Starting from this premise, from a«sociological perspective» it is proposed a classification of the strata of the city according to the pooled weighted average and candidate as elite/non elite, to analyze the electoral trends in terms of political preferences of each stratum. It also seeks to identify causal combinations that consents the election of a mayor, taking into account variables such as the profil elite/non elite of the candidates, levels of fragmentation in both segments of candidatures and finally, the dominance that each achieved in the different communes of the city.